Protection of Children during Armed Conflicts According to the Rules of International Humanitarian Law and the Laws of Arab States - Abdalnaby, Islam (Journal of Legal Sciences, 2025)
The world has been and continues to be a theater of wars that inflict physical and moral damage on human beings. Since the establishment of the United Nations, the world has been searching for solutions to the crises caused by wars. The international community has addressed this problem by concluding numerous international agreements to deal with situations of war and armed conflict, including, for example, the four Geneva Conventions of 1949 and their two Additional Protocols of 1977, which included many provisions seeking to regulate the rights of civilians, children, and even participants in armed conflict, with the aim of limiting the harm that may befall them. The Arab Gulf states have also sought to provide greater protection for children in situations of armed conflict by enacting domestic laws to protect children. However, despite these provisions, they have not provided adequate protection for children during wars and armed conflicts. This has prompted us to prepare this research to develop an Arab mechanism through which adequate protection can be provided to children during armed conflicts at the Arab level, in the hope that it will serve as a nucleus for providing more protection to children at the international level.